THE RELATIONSHIP BETWEEN GOVERNMENT ACCOUNTING LITERACY AND SMART CITIZENSHIP: A THEORETICAL STUDY BASED ON E-GOVERNMENT AND MUNICIPAL WEBSITES (Third Sector Social Economic Review, 2024)
The primary objective of this study is to conceptually examine the impact of public accounting literacy on smart citizenship. Additionally, the research involves a quantitative analysis of the number and content of services provided by municipalities through e-government platforms in Turkey, along with an evaluation of accounting information on municipal websites within the same scope. The study explores whether the public accounting literacy of citizens can enhance smart citizenship conceptually. The convergence of citizen-focused smart city initiatives with citizens who possess public accounting literacy can effectively stimulate participation and encourage collaborative design initiatives. Findings suggest that municipalities tend to maintain greater control in e-government service delivery, perceiving citizens as passive consumers. The presence or absence of accounting information on municipal websites does not significantly impact the number of e-government services provided. However, it is noteworthy that accounting information has a meaningful and positive effect on the number of services offered through e-government platforms for districts or municipalities. Simplifying and summarizing accounting information on municipal websites in a manner understandable to citizens is considered a crucial initial step in facilitating public understanding of such information.
Keywords: Government accounting literacy; Smart cities; Smart citizenship.